2019
DOI: 10.1111/jerd.12538
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue changes after connective tissue grafts around immediately placed and restored dental implants in the esthetic zone: A systematic review and meta‐analysis

Abstract: Objective: The aim of this systematic review and meta-analysis was to evaluate the soft tissue outcomes of connective tissue graft (CTG) combined with immediate implant placement and restoration (IIPR) in the esthetic zone.Materials and methods: Following the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement, randomized controlled trials (RCTs) were searched for in electronic databases and complemented by hand searching. The risk of bias was assessed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 39 publications
6
27
0
2
Order By: Relevance
“…41,42 A recent systematic review described the CTG as a beneficial treatment in postextractive implants; however, the morbidity associated with an autogenous soft tissue graft must be considered. 43 It is also possible to verify that at the fourth month of treatment part of the previously linear and volumetric variation had recovered, which might be explained by the delivery of provisional restorations.…”
Section: Discussionmentioning
confidence: 97%
“…41,42 A recent systematic review described the CTG as a beneficial treatment in postextractive implants; however, the morbidity associated with an autogenous soft tissue graft must be considered. 43 It is also possible to verify that at the fourth month of treatment part of the previously linear and volumetric variation had recovered, which might be explained by the delivery of provisional restorations.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, thick soft tissue can even mask and hide alveolar bone loss on the buccal side of implants [12,13,15]. Therefore, soft tissue augmentation is recommended in esthetical regions where a certain amount of buccal bone remodeling is expected, like immediate implant placement in situations with thin biotype or thin buccal bone plate [17,18].…”
Section: Esthetic Appearancementioning
confidence: 99%
“…This, interestingly, applies to all tissue phenotypes. [34][35][36][37][38][39] Placing the CTG at the end of the immediate implant procedure allows for proper control of the space around the abutment. It also avoids contamination and desiccation of the graft.…”
Section: Connective Tissue Graft From Tuberositymentioning
confidence: 99%
“…Several studies have demonstrated the benefits of placing subepithelial connective tissue grafts (CTG) after implant insertion, especially when the implant is placed immediately. This, interestingly, applies to all tissue phenotypes 34‐39 . Placing the CTG at the end of the immediate implant procedure allows for proper control of the space around the abutment.…”
Section: The Predictable Immediate Implant Conceptmentioning
confidence: 99%